The legal practice in international law and European community law : a Spanish perspective - Jiménez Piernas, Carlos (Martinus Nijhoff Publishers, 2007)
Divided into five parts, this work offers a Spanish perspective on contemporary practice in international law and European Community law by practitioners such as registrars, judges and magistrates serving on national and international courts, as well as advocates practicing in these courts, senior officials, government advisers and academics.